2017
DOI: 10.4149/bll_2016_126
|View full text |Cite
|
Sign up to set email alerts
|

May argyrophilic nucleolar organizing region-associated protein synthesis be used for selecting the most reliable dose of drugs such as rhamnetin in cancer treatments?

Abstract: Rhamnetin has an important role in preventing cancer formation. Our study showed that mean AgNOR numbers and TAA/NA values may be used also as biomarkers for evaluating the success rate of the performed therapeutic strategy and accurate dose selection for the management of the disease (Tab. 3, Fig. 3, Ref. 45).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…Although it is known that it is not toxic in rats even at a dose of 3000 mg/kg body weight, its bioavailability and stability in the cell is very low (27). Numerous scientifi c reports showed that C. mas L has anti-tumoral activity and targets different oncogenic pathways (18). They reported that C. mas L had a cytotoxic effect on tumor cells, but did not fully approach the antitumor activity in terms of apoptosis and angiogenesis (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is known that it is not toxic in rats even at a dose of 3000 mg/kg body weight, its bioavailability and stability in the cell is very low (27). Numerous scientifi c reports showed that C. mas L has anti-tumoral activity and targets different oncogenic pathways (18). They reported that C. mas L had a cytotoxic effect on tumor cells, but did not fully approach the antitumor activity in terms of apoptosis and angiogenesis (28).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify new biomarkers to differentiate benign and malignant lesions. In addition, the selection of the most reliable therapeutic strategy for cancer treatment is very important for the management of the treatment strategy and to improve success (16,18,36). We aimed to determine the average number of AgNOR in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The simplicity and cost-effectiveness of the present AgNOR technique make this a valuable diagnostic method. 14,15 In addition to the detection of the number, size and shape of AgNORs, the measurement of the total AgNOR area and the total nuclear area used for the calculation of the TAA/TNA ratio is also important. 14 Calculation of the TAA/TNA ratio reflects the protein synthesis capacity of the cells, which provides information about the metabolic and proliferative activity of each cell.…”
Section: Introductionmentioning
confidence: 99%
“…EAC cells were obtained from Department of Anatomy, Faculty of Medicine, Erciyes University, Kayseri, Turkey [24] . The tumor cells were maintained in our laboratory by serial intraperitoneal passage in male BALB-c mice for 7-10 days.…”
Section: Eac and Stock Animalsmentioning
confidence: 99%